Small stories as curated formats on social media: The intersection of affordances, values & practices. (November 2021) - Georgakopoulou, Alex
Abstract: In this article, I focus on the design of stories as a specific feature, integrated into the spatial architecture of platform affordances (i.e. on Snapchat, Instagram, Facebook, Weibo. I argue for the need to interrogate such stories as curated, socio-technical formats, that is, as recogniseable and normative co-patternings of media-afforded ways of telling & types of teller. I show a methodological and analytical way of doing so, underpinned by a technographic perspective to stories that tracks media affordances, discourses about stories as features and communicative practices. I illustrate this approach with reference to three directives (cf. Preferential conditions, prompts) to users that my analysis attested to (Georgakopoulou, 2019; Georgakopoulou et al., 2020). These directives shape the types of stories told (i.e. sharing life-in-the-moment), the audience's mode of engagement in them (i.e. quantified viewing) and the tellers' self-presentation (i.e. authenticity). I specifically focus on the first directive of sharing-life-in-the-moment and consider its implications for the kinds of (in)visibilities of specific types of tellings, tales and tellers that has the potential to create. This line of inquiry, I suggest programmatically, can be productively integrated into critical digital literacies work and, subsequently, feed into discussions with (language) education and other non-academic stakeholders.